The history of life : a very short introduction - Benton, M. J. (Michael J.) (Very short introductions, 2008)
This Very Short Introduction presents a succinct and accessible guide to the key episodes in the story of life on earth - from the very origins of life four million years ago to the extraordinary diversity of species around the globe today. - ;There are few stories more remarkable than the evolution of life on earth. This Very Short Introduction presents a succinct guide to the key episodes in that story - from the very origins of life four million years ago to the extraordinary diversity of species around the globe today. Beginning with an explanation of the controversies surrounding the birth of life itself, each following chapter tells of a major breakthrough that made new forms of life possible: including sex and multicellularity, hard skeletons, and the move to land. Along the way, we witness the greatest mass extinction, the first forests, the rise of modern ecosystems, and, most recently, conscious humans. Introducing ideas from a range of scientific disciplines, from evolutionary biology and earth history, to geochemistry, palaeontology, and systematics, Michael Benton explains how modern science pieces the evidence in this vast evolutionary puzzle together, to build up an accessible and up-to-date picture of the key developments in the history of life on earth. -.